2016
DOI: 10.1016/j.ridd.2016.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Impact of practice leadership management style on staff experience in services for people with intellectual disability and challenging behaviour: A further examination and partial replication

Abstract: These findings suggest further research is needed to examine the potential of interventions in frontline management/leadership practice to improve staff experience of working in challenging environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 15 publications
0
19
1
1
Order By: Relevance
“…Bigby and Beadle‐Brown () report that in terms of explaining why the quality of support is variable, the areas with the most evidence include a positive, person‐centred staff culture and staff receiving practice leadership. In addition to having clear aims and values to guide the work of staff and a shared vision that focuses on the quality of life of the people supported, those providing practice leadership need to have both a clear understanding of active support and other person‐centred approaches and skills in working in this way in order to lead their team (Beadle‐Brown et al., , ; Deveau & McGill, and Mansell & Beadle‐Brown, ). Most managers did not report a strong shared vision or aims for the service and whilst this should be led by senior management (Mansell & Beadle‐Brown, ), mangers did not seem to relate what they were trying to achieve to the aims and values of the organization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bigby and Beadle‐Brown () report that in terms of explaining why the quality of support is variable, the areas with the most evidence include a positive, person‐centred staff culture and staff receiving practice leadership. In addition to having clear aims and values to guide the work of staff and a shared vision that focuses on the quality of life of the people supported, those providing practice leadership need to have both a clear understanding of active support and other person‐centred approaches and skills in working in this way in order to lead their team (Beadle‐Brown et al., , ; Deveau & McGill, and Mansell & Beadle‐Brown, ). Most managers did not report a strong shared vision or aims for the service and whilst this should be led by senior management (Mansell & Beadle‐Brown, ), mangers did not seem to relate what they were trying to achieve to the aims and values of the organization.…”
Section: Discussionmentioning
confidence: 99%
“…The one thing the present authors do know is that managers are critical to providing the support and motivation required to enable staff to work using enabling approaches (such as active support) (Mansell & Beadle‐Brown, ). Particularly important appears to be whether staff are receiving practice leadership, which involves managers leading by example, modelling, coaching, reviewing how support is being provided through supervision and team meetings and organizing staff to deliver support when and how the people need and like it (Beadle‐Brown, Bigby, & Bould, ; Beadle‐Brown et al., ; Deveau & McGill, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, a particular style of management focused upon developing staff practice called ‘practice leadership’ (and good general management) are important factors for implementing 'active support' (Beadle‐Brown et al, ). Frontline managers also have an important role in ameliorating potential negative experiences for staff when they have to support service users who may show behaviour described as challenging (Deveau & McGill, , ).…”
Section: Introductionmentioning
confidence: 99%
“…High turnover of staff clearly presents a problem for providing staff with PL to develop and maintain high levels of skill in managing the challenging behaviours that may be shown by people with learning disabilities. Previous research results have been inconsistent regarding the relationship between PL and measures of staff turnover (Deveau & McGill, ). This study showed both greater RM contact and PL were associated with less likelihood to leave, and this relationship was a little stronger with PL.…”
Section: Discussionmentioning
confidence: 89%
“…Support from immediate co-workers and especially the first line manager is important in ameliorating such negative experiences (Hatton et al, 1999;Rose et al, 2004). Also important in reducing negative experiences for staff is a particular style of frontline management, practice leadership (Deveau & McGill, 2014& Deveau & McGill 2016a.…”
Section: Introductionmentioning
confidence: 99%